Bilateral peroneal nerve paralysis in agricultural workers: three case reports. (21st October 2021) - Tuna, M; Satis, S
Summary: The peroneal nerve can be injured due to direct trauma or non-traumatic causes, with the injury mostly occurring between the fibular head and neck and mostly unilateral. This injury mostly results from prolonged squatting, cross-legged sitting or sitting with one foot tucked under the other leg. In this report, we present three agricultural workers with a history of prolonged squatting who developed bilateral foot drop due to bilateral peroneal nerve injury, two of whom recovered almost completely after physical therapy, and one remained disabled. Agricultural workers should be advised to avoid prolonged squatting for more than 2 h, to extend the knee and to strengthen the muscles around the knee in order to prevent neuropathy.